Health systems strengthening to arrest the global disability burden: empirical development of prioritised components for a global strategy for improving musculoskeletal health. Issue 6 (18th June 2021) - Briggs, Andrew M; Huckel Schneider, Carmen; Slater, Helen; Jordan, Joanne E; Parambath, Sarika; Young, James J; Sharma, Saurab; Kopansky-Giles, Deborah; Mishrra, Swatee; Akesson, Kristina E; Ali, Nuzhat; Belton, Joletta; et al.
Abstract : Introduction: Despite the profound burden of disease, a strategic global response to optimise musculoskeletal (MSK) health and guide national-level health systems strengthening priorities remains absent. Auspiced by the Global Alliance for Musculoskeletal Health (G-MUSC), we aimed to empirically derive requisite priorities and components of a strategic response to guide global and national-level action on MSK health. Methods: Design: mixed-methods, three-phase design. Phase 1: qualitative study with international key informants (KIs), including patient representatives and people with lived experience. KIs characterised the contemporary landscape for MSK health and priorities for a global strategic response. Phase 2: scoping review of national health policies to identify contemporary MSK policy trends and foci. Phase 3: informed by phases 1–2, was a global eDelphi where multisectoral panellists rated and iterated a framework of priorities and detailed components/actions. Results: Phase 1: 31 KIs representing 25 organisations were sampled from 20 countries (40% low and middle income (LMIC)). Inductively derived themes were used to construct a logic model to underpin latter phases, consisting of five guiding principles, eight strategic priority areas and seven accelerators for action. Phase 2: of the 165 documents identified, 41 (24.8%) from 22 countries (88% high-income countries) and 2 regions met the inclusion criteria. Eight overarching policy themes, supported by 47 subthemes, were derived, aligning closely with the logic model. Phase 3: 674 panellists from 72 countries (46% LMICs) participated in round 1 and 439 (65%) in round 2 of the eDelphi. Fifty-nine components were retained with 10 (17%) identified as essential for health systems. 97.6% and 94.8% agreed or strongly agreed the framework was valuable and credible, respectively, for health systems strengthening. Conclusion: An empirically derived framework, co-designed and strongly supported by multisectoral stakeholders, can now be used as a blueprint for global and country-level responses to improve MSK health and prioritise system strengthening initiatives.